MEDITASI SEBAGAI PEMBENTUKAN DIRI ORANG MUDA KATOLIK (USIA 13-24 TAHUN) - Ginting, Pelta (IN VERITATE LUX, 2019)
Young people are the hope and future for the church and society. Young people have potential within them. Young people have characteristics, uniqueness, qualities, talents and interests that must be considered. To become Catholic Young People (OMK) as expected by the Church, youth self-formation can be done by applying one method, namely meditation prayer. Meditative prayer is focusing the heart and mind on God. Nowadays, the role of meditation prayer for a healthy spiritual and physical life is increasingly being recognized in the formation of young people. Prayer is the main axis of life towards God. Young people cannot develop into Catholics who are truly close to God and others if they forget to pray. Praying not only refreshes and enriches the mind but also deepens physical life. This fact can be seen in everyday life, many people pray for health and healing from all illnesses and suffering, in the Holy Bible it can be seen only by people who believe in Jesus Christ, it is clearly visible the relationship between faith and happiness. The method used in this research uses Library Research/libraries by using and studying books and writings related to the influence of meditation in the self-formation of young people.